Commentary on Otto Kernberg's "Some Implications of New Developments in Neurobiology for Psychoanalytic Object Relations Theory". Issue 1 (2nd January 2022) - Sandberg, Larry S.
ABSTRACT: Otto Kernberg reaffirms the central motivational role of affects in his object relations theory by incorporating the seminal work of Jaak Panksepp's affective neuroscience. At the same time, he retains a dual drive model that posits libido and aggression as both a supraordinate level of development and etiologic of all unconscious conflict. The neuroscience he relies upon suggests alternative perspectives. Kernberg's dynamic unconscious postulates the essential role of declarative memory regarding the neurotic use of repression and the more primitive dissociative defenses in sicker patients. This view is compared to that of Mucci, who sees dissociation as procedural memory. I suggest a broader conceptualization of the dynamic unconscious that takes into account, as Kernberg states, its infantile origins and incorporates the nonverbal symbolic realm of experience.